Pengaruh Inflasi Dan Pendapatan Perkapita Terhadap Konsumsi Rumah Tangga di Indonesia - Asrida; Haryani; Hakim Muttaqim; Ernita (Lentera : Jurnal Ilmiah Sains, Teknologi, Ekonomi, Sosial, dan Budaya, 2023)
The research aims to explain the influence of inflation and and per capita income on household consumption in Indonesia in 1993-2023. The type of data in this research is secondary data using quantitative research methods and multiple linear regression models. The results of this study state that inflation has no effect on household consumption in Indonesia. Per capita income influences household consumption in Indonesia. Simoultaneously, inflation and per capita income influence household consumption in Indonesia.